The road transportation industry in Brazil: Market structure, performance and government regulation - Newton de Castro (Institute for Applied Economic Research (ipea), 2015)
This study summarizes some of the most important characteristics of the road transportation industry, and presents a discussion of its performance. The main objective is identifying areas where government action may be needed in order to correct market failures or to remove inadequate regulation. In the first part, the structure, size and economic relevance of the industry are presented. There is also a brief review of government regulation. The second part is dedicated to analyzing the industry performance, including: investment levels; fleet renewal and adequacy; energy consumption and conservation possibilities; cost structures and freight rates; the impact of government regulation; and factors concerning efficiency and growth. Suggestions for further studies are also outlined.
Keywords: 330